Leaders for the Banking Industry: An investigation on effective leadership. - Ukwatta Liyanage Thamara Priyanthi Gunasekare (KINERJA, 2021)
Leadership is critical in achieving performance and yet not exhausted, keeping scholars to uncover more findings on effective leadership styles. This study expected to identify the effective leadership style for enhanced employee performance in the banking industry in Sri Lanka. The banking industry has a unique work environment that stresses performance targets, long working hours, and error-free transactions while making the customers happy. Thus, leadership is a critical stimulus that this study focused on. The findings illustrate that transformational leadership style is the most present style among the bankers in Sri Lanka, and employee performance is above average with transformational leaders. Overall, scores in the transformational leadership style were found to be strongly correlated with employee performance. The results suggest that supervisors in the banking sector need to use a lot of transformational leadership behaviours or rather embrace a transactional leadership style. The implications of the study are significant in HR practices like recruiting and training managers as leaders in the banking sector.Keywords: leadership style, transformational leadership, MLQ, transactional leadership, employee performance).